Peningkatan hasil belajar matematika materi jaring-jaring kubus dan balok menggunakan model problem based learning di Kelas IV Sekolah Dasar - Rahmasiwi, Dwinda Susi; Maharani, Swasti; Hartini, Suliyawati (Program Studi Pendidikan Matematika, Universitas Nusantara PGRI Kediri, 2023)
The purpose of this research is to improve the results of learning mathematics on the material of nets of cubes and blocks in class IV students at SDN Karangtengah Prandon 1 using the Problem Based Learning learning model. This type of research is classroom action research which is carried out in 2 cycles. The subjects used in this study were class IV students at SDN Karangtengah Prandon 1, which consisted of 11 students. The independent variable used in this research is Problem Based Learning and the dependent variable is the result of learning mathematics. The techniques used in this research are tests, observations and interviews. While the analysis techniques used in this study were quantitative and qualitative in the form of observations made and the percentage of student learning outcomes from the pre-cycle and after the cycle. Based on the research results, it can be concluded that learning by using the Problem Based Learning Model in mathematics lessons, the material for nets of cubes and blocks of student learning outcomes can be improved. The increase in learning outcomes in the pre-cycle was 27.2%, the first cycle was 63.6% and the second cycle was 91%. This assessment was said to be successful because the learning outcomes reached the mastery indicator, namely ≥ 80% of the class average with KKM ≥ 70.